KONTRIBUSI MAHASISWA DALAM MEWUJUDKAN SUNGAI DAN JALANAN YANG BERSIH DI DESA REWWIN - Negara, Dharma Setiawan; Dipaajiblana; El-Yunusi, Muhammad Yusron Maulana; Darmawan, Didit; Hardyansah, Rommy (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Waste accumulation in urban areas, such as Rewwin village Waru District, Sidoarjo Regency, poses a significant environmental challenge, posing a risk of flooding, water pollution, and the spread of disease. This situation demands collective action and effective waste management. This collaboration focused on identifying students' concrete contributions to the effort to create clean rivers and streets in Rewwin Village. The goal was to foster shared awareness, instill clean living habits, and support the creation of a healthy and sustainable environment. The method used was Participatory Action Research (PAR), which involved the active participation of students and residents through observation and collaborative implementation of field actions. During the implementation phase, the collaborative river and street cleaning action demonstrated high community enthusiasm. The students' physical contributions, from cleaning up small plastic waste on the streets to extensively cleaning water hyacinths on the riverbanks, served as a concrete example and a driving force for cultural change. The result of this collaborative activity was clean streets and rivers, which went from dirty to clean. The conclusion of this activity was that the main objective of the physical street and river cleaning was successfully achieved, as evidenced by the successful collaboration and high level of community participation. This activity also succeeded in strengthening solidarity and fostering a sense of collective responsibility. It is recommended that similar activities be carried out regularly and periodically to maintain the sustainability of the program and further strengthen social bonds among residents.